أثر أبعاد الثقافة التنظيمية علي مستوي أداء العاملين بمركز الكلي بمستشفى بن سيناء سرت (Economic studies journal, 2022)
This study aims to identify the impact of the dimensions of organizational culture on the level of performance of workers at the Kidney Center at Ben Sina Hospital Sirte. In order to achieve that, hypotheses were developed and tested by analyzing Multiple regression, and the analysis was conducted through the primary data collected by means of a questionnaire, and distributed to all members of the Kidney Center at Ben Sina Hospital Sirte as comprehensive study. The descriptive approach was used to describe the phenomenon and analyze the data related to the study variables. According to the findings, it was found that there are high levels of practicing all types of organizational culture (the culture of power, the culture of systems and roles, the culture of achievement, the culture of human empathy) in the Kidney Center. The job was also high, in addition to a very strong correlation and an impact of organizational culture on improving job performance. The dimensions of achievement culture and strength culture had a very strong impact on job performance and that they explain (89.7%) of the variance in performance, while the dimension did not. The culture of systems and the culture of human empathy have an impact on performance when measuring the dimensions that have the most impact on performance combined. Based on the results, some recommendations were suggested, including the emphasis on increasing the degree of interest in organizational culture and educating employees about it, because of its contribution to improving the level of performance of employees, and continuous attention to the elements that constitute culture by identifying its strengths and working to strengthen it, and identifying weaknesses and work to develop and strengthen them, and work to ensure that there is consensus and partnership between employees and management in the center around values, to unify the organizational culture that determines the pattern of relationships between individuals, which will contribute to increasing the degree of commitment to the goals of the center.
Keywords: organizational culture; culture of power; culture of systems and roles; culture of achievement; culture of human empathy; job performance; total center